Raindrop size distribution extracted from rain attenuation data - Omar AbdulKabeer, Hatem AlMokhtar (2008)
Attenuation due to rain plays a significant role in the terrestrial and earthspace communication systems especially at frequencies above 10 GHz. Although models proposed by ITU-R for the prediction of rain attenuation give a good estimation about the signal attenuation caused by rain for temperate regions, recent studies shows that it underestimates the same tropical regions. Tropical regions are characterized by high intensity rainfall, enhanced frequency of rain occurrence and the increased presence of large raindrop when compared with temperate climates. This project will look into the prediction of raindrop size distribution by analyzed and convert the summarized collected data on rain attenuation. The summarized data are taken from point to point microwave link measurements at Skudai, Johor Bahru. The data needs to be taken into consideration on many aspects that will involve in wave propagation phenomena. An accurate estimation of the drop size distribution (DSD) is essential in the interval of rainfall parameters from microwave measurement and in the modeling of microwave propagation through rain. Information of raindrop size distribution (DSD) is important for prediction of the microwave signal attenuation due to rain. Drop size distribution is one of major parameters that effects on microwave signal degradation due to rain, detail information on (DSD) leads better accuracy on the attenuation prediction due to rain thus, (DSD) profile is extracted from locally collected rain attenuation data base at operating frequencies 26 and 38 GHz. The Singapore model of drop size distribution gives better prediction for rain specific attenuation due to the rain attenuation data was collected in Johor.